2010
DOI: 10.1080/14786411003754363
|View full text |Cite
|
Sign up to set email alerts
|

Crocetin from the tubular calyx ofNyctanthes arbor-tristis

Abstract: A carotenoid aglycone Ag-NY1 was isolated from the orange coloured tubular calyx of flowers of Nyctanthes arbor-tristis. The elucidation of the structure through a detailed spectroscopic study revealed that the carotenoid molecule is crocetin, which is the major aglycone present in the stigma of Crocus sativus. The compound exhibited a good membrane stabilising activity as compared to the corresponding glycoside crocin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Peak 2 (Figure 2(b)) (RT = 20.509 min, λ = 440 nm, and MW = 652.27) (Figure 4) had [M + H] + at m/z 653.1994 and was identified as carotenoid, glycosides, namely, β -monogentiobioside ester of α -Crocetin (or Crocin-3) with loss of 1,5-anhydro-D-glucitol that ion appeared at m/z 165.0651 and m/z 491 carotenoid ester with other fragments at m/z 459, 315, and 147 [22]. The reddish-orange coloured tubular calyx of flower of N. arbortristis is due to carotenoid pigments (Crocetin and its derivatives) which are reported from the flowers of this plant [22, 23]. …”
Section: Resultsmentioning
confidence: 99%
“…Peak 2 (Figure 2(b)) (RT = 20.509 min, λ = 440 nm, and MW = 652.27) (Figure 4) had [M + H] + at m/z 653.1994 and was identified as carotenoid, glycosides, namely, β -monogentiobioside ester of α -Crocetin (or Crocin-3) with loss of 1,5-anhydro-D-glucitol that ion appeared at m/z 165.0651 and m/z 491 carotenoid ester with other fragments at m/z 459, 315, and 147 [22]. The reddish-orange coloured tubular calyx of flower of N. arbortristis is due to carotenoid pigments (Crocetin and its derivatives) which are reported from the flowers of this plant [22, 23]. …”
Section: Resultsmentioning
confidence: 99%
“…Saffron is a Chinese traditional herb, and Crocetin is the major constituent of saffron, which has recently found to have multiple pharmacological effects including anticancer [15][16][17]. However, the effects of Crocetin on asthma as well as the underlying mechanisms have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The elucidation of the structure through a detailed spectroscopic study revealed that the carotenoid molecule is Crocetin, which is the major aglycone present in the stigma of Crocus sativus. The compound exhibited a good membrane stabilizing activity as compared to the corresponding glycoside crocin (Gadgoli and Shelke, 2010). The decoction of the leaves of Nyctanthes arbortristis Linn (Harsingar) is widely used in Ayurveda system of medicine for the treatment of sciatica, arthritis, fevers, and various painful conditions and as laxative.…”
Section: Phytochemical and Pharmacogical And Tissue Culture Study Of mentioning
confidence: 99%